2021
DOI: 10.3390/metabo11110717
|View full text |Cite
|
Sign up to set email alerts
|

Human Fecal Metabolome Reflects Differences in Body Mass Index, Physical Fitness, and Blood Lipoproteins in Healthy Older Adults

Abstract: This study investigated how body mass index (BMI), physical fitness, and blood plasma lipoprotein levels are related to the fecal metabolome in older adults. The fecal metabolome data were acquired using proton nuclear magnetic resonance spectroscopy and gas chromatography–mass spectrometry on 163 healthy older adults (65–80 years old, 80 females and 83 males). Overweight and obese subjects (BMI ≥ 27) showed higher levels of fecal amino acids (AAs) (valine, alanine, and phenylalanine) compared to normal-weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
(87 reference statements)
4
5
0
Order By: Relevance
“…Moreover, the obtained metabolic fingerprints exhibited meaningful pathophysiological correlations with a whole range of relevant anthropometric and clinical parameters for (childhood) overweight and obesity. Indeed, the correlations found in this study showed similar (62,63) or improved (54,63) Spearman ρ-values (up to 0.5) compared to earlier work. For example, we observed a correlation between the fecal metabolome, BMI and blood lipid levels (Spearman ρvalues of up to 0.4), in line with previous results concerning the fecal metabolome of obese adults (63).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, the obtained metabolic fingerprints exhibited meaningful pathophysiological correlations with a whole range of relevant anthropometric and clinical parameters for (childhood) overweight and obesity. Indeed, the correlations found in this study showed similar (62,63) or improved (54,63) Spearman ρ-values (up to 0.5) compared to earlier work. For example, we observed a correlation between the fecal metabolome, BMI and blood lipid levels (Spearman ρvalues of up to 0.4), in line with previous results concerning the fecal metabolome of obese adults (63).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, the correlations found in this study showed similar (62,63) or improved (54,63) Spearman ρ-values (up to 0.5) compared to earlier work. For example, we observed a correlation between the fecal metabolome, BMI and blood lipid levels (Spearman ρvalues of up to 0.4), in line with previous results concerning the fecal metabolome of obese adults (63). Similarly, Spearman ρ-values of up to 0.3 for fecal microbiome diversity with BMI and glycemic and lipid measurements in adults were recently reported (54), while our MetaSAMP ® s reached ρ-values of up to 0.6 regarding glycemic measurements such as glucose and insulin.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have shown that subjects at high risk of diabetes have higher levels of fecal amino acid, and that the impaired metabolism of the organism caused by obesity also leads to an increase in fecal amino acid levels. For example, higher levels of alanine have been found in the feces of overweight and obese subjects ( 43 ). Studies in patients with diabetes and metabolic syndrome have found that the concentration of fecal alanine increased with the development of the disease ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…NMR assay of fecal metabolome can allow health and fitness coverage based on biochemical compositions. Amongst the metabolites in the fecal metabolome such as amino acids, fatty acids, lipoproteins, chemical markers of fitness, many metabolites were observed also in the blood plasma ( Cui et al, 2021 ). In order to track the influence of SARS-CoV-2, fecal metabolome was analyzed by gas chromatography coupled with mass spectrometry (GC-MS) exploring 205 metabolites.…”
Section: Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%